A Simple Reminder that Increases Levels of Physical Activity and Improves Glycemic Control in Patients with Type 2 Diabetes - Soltanova, Lala; Saglamer, Burcu; Durcan, Emre; Uysal, Serhat; Muradov, Ilkin; Kocaman, Banu Betul; Gönen, Mustafa Sait; Damci, Taner (Cerrahpaşa Medical Journal, 2025)
Objective: Daily step count is widely accepted as a valuable indicator of physical activity level. The study aimed to test whether it was possible to establish and/or increase patients’ connectedness with the pedometer data in their smartphones and smartwatches through a short reminder. Methods: The study included 70 patients whose daily average step count was checked, who provided good glycemic control and whose treatment would not be changed (HbA1c < 7.5%). Demographic and laboratory data of the patients, average step counts in the last 6 months, and smartphone models were recorded, and these data were compared with the data after 6 months. Results: The study included 70 diabetic patients, 30 women and 40 men. The mean number of steps increased from 5587.8 ± 2959 at baseline to 6219 ± 3001 after 6 months. The number of steps increased from 4692 ± 2402 to 6502 ± 2813 in 47 (62%) patients with brief reminder (P < .001). There is a correlation between the increase in the number of steps and the decrease in HbA1c (P < .05). Conclusion: This study demonstrates that a short reminder recited by physicians during the diabetes outpatient clinics visits aimed at increasing connectedness to smartphone/watch daily step count data leads to an increase in daily step count in most of the patients over 6 months. The increase in the daily step count correlated significantly with a decrease in HbA1c levels.